Shallow crustal structure of eastern trans-Mexican volcanic belt: Gravity and magnetic constraints - Campos-Enríquez, J.O.; Vázquez-Domínguez, C.; Keppie, J.D.; Quintero, W.; Espinosa-Cardeña, J.M. (Journal of volcanology and geothermal research, 2024)
The Trans-Mexican Volcanic Belt (TMVB) stretches from the Gulf of Mexico up to Pacific Ocean. Its eastern portion is in contact with the Mixteca and Oaxaca terranes (to the south), and with the Sierra Madre Oriental (SMOr) thrust and fold belt (to the north). We conducted a gravity and magnetic study to establish the tectonic fabric and major characteristics of the basement beneath the volcanic and sedimentary cover of this volcanic province. Accordingly, we have established the existence of NE-, W-, and NW-trending lineaments. The most abundant lineaments have mean NW-SE orientation and mark portions of the Rio Actopan and Agua Blanca faults along the southern rim of the Sierra Madre Oriental, and the thrust front of the Cordoba platform. Noteworthy, the most conspicuous set of NW-SE lineaments is interpreted as associated with a major tectonic weakness zone from eastern TMVB that extends from the Apan monogenetic volcanic field, in the northwest, to the Pico de Orizaba, in the southeast, where it merges with thrust front of the Cordoba platform. Our gravity modelling indicates these lineaments are expressions of faults that juxtapose blocks of different crystalline basements. Here we interpret, that this regional tectonic lineament controlled the emplacement of TMVB Cenozoic volcanism (i.e., Acoculco caldera, Tlaxco range, Cerro Grande volcano, Las Derrumbadas domes. A major depression occupies the Mixteca-Oaxaca contact zone with the Huastecan pre-Mesozoic crystalline basement that underlies the Sierra Madre Oriental thrust and fold belt. Convergence in the northern Tehuacán Valley of the major lineament here established and faults of southern Mexico (i.e., the Oaxaca Fault) indicates a change of tectonic regime from a transpression in the south, to an extension in eastern TMVB. •Crustal structure geophysical study of eastern Trans-Mexican Volcanic Belt.•Gravity and magnetics delineate a major tectonic weakness zone in eastern TMVB.•Lineaments are expression of faults that juxtapose different tectonic terranes.•Contact between the Oaxaca, Mixteca terranes with the Hustecan orogen.•Volcanism in Eastern TMVB was controled by a NW-SE major weakness zone.